2006
DOI: 10.1128/jb.00124-06
|View full text |Cite
|
Sign up to set email alerts
|

Complete Genome Sequence of Yersinia pestis Strains Antiqua and Nepal516: Evidence of Gene Reduction in an Emerging Pathogen

Abstract: Yersinia pestis, the causative agent of bubonic and pneumonic plagues, has undergone detailed study at the molecular level. To further investigate the genomic diversity among this group and to help characterize lineages of the plague organism that have no sequenced members, we present here the genomes of two isolates of the "classical" antiqua biovar, strains Antiqua and Nepal516

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
128
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(136 citation statements)
references
References 46 publications
7
128
0
1
Order By: Relevance
“…In all of the Y. pestis strains sequenced to date (CO92, KIM10+, 91001, Antiqua, Nepal516 and Angola) (Chain et al, 2006;Deng et al, 2002;Parkhill et al, 2001;Song et al, 2004), iucA contains a mutation which splits the gene into two ORFs [ Fig. 1; iucA1 (y3380) and iucA2 (y3381) in KIM] with the corresponding proteins IucA1 being 62 % similar to residues 1-184 and IucA2 72 % similar to residues 219-575 of E. coli IucA, respectively (Fig.…”
Section: Sequence Analysis Of the Aerobactin Locusmentioning
confidence: 99%
“…In all of the Y. pestis strains sequenced to date (CO92, KIM10+, 91001, Antiqua, Nepal516 and Angola) (Chain et al, 2006;Deng et al, 2002;Parkhill et al, 2001;Song et al, 2004), iucA contains a mutation which splits the gene into two ORFs [ Fig. 1; iucA1 (y3380) and iucA2 (y3381) in KIM] with the corresponding proteins IucA1 being 62 % similar to residues 1-184 and IucA2 72 % similar to residues 219-575 of E. coli IucA, respectively (Fig.…”
Section: Sequence Analysis Of the Aerobactin Locusmentioning
confidence: 99%
“…Comparing the genomes of strains D106004 and D182038 and six Y. pestis genomes sequenced previously, [7][8][9][10] we found that all Y. pestis strains had 31 Fse I restriction sites except for Chinese strain 91001 and strain Nepal 516 ( Table 2 ). Strain Nepal 516 had 29 sites and the 2 missed Fse I sites were located in a pathogenic island that was deleted.…”
Section: Resultsmentioning
confidence: 98%
“…1; see also Table S2 in the supplemental material). All Y. pestis strains lacked or had a mutated yapX gene, highlighting a reductive evolutionary process that is typical for this species (39). Interestingly, all 13 North American strains of Y. pestis were biotype Orientalis strains and had lost yapV, even though the biotype Orientalis isolates from Asia and South America still carried yapV (43,44).…”
Section: Resultsmentioning
confidence: 99%
“…YapV shares 86% amino acid identity with YapK (y0567). Comparisons of Y. pestis and Y. pseudotuberculosis genomes (38)(39)(40)(41)(42) revealed that most of the genomes carried a yapV gene as well as up to three paralogous genes or pseudogenes, designated yapK, yapJ, and yapX (see Fig. S2 and Table S2 in the supplemental material).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation